Particle size analysis of two distinct classes of wheat flour by sieving - Patwa, Abhay; Malcolm, Blake; Wilson, Jonathan; Ambrose, R. P. Kingsly (My University, 2014)
The most commonly used method for particle size analysis of wheat flour in the grain industry is a sieve shaker following either the ASABE or AACC standard. This study involved the determination of mean particle size of flour from two different classes of wheat, hard red winter (HRW) and soft white (SW), at sieving times of 8, 10, 12, 14, 16, and 18 min. Particle size measured by sieve analysis was compared with size as measured using laser diffraction. It was found that sieving time and wheat class had a significant effect on the measured final particle size. Increase in sieving time reduced the calculated average particle size of the flour. The mean particle size for HRW and SW flour was 110.98 µm and 570.29 µm, respectively, at 14 min of sieving. The mean particle size as measured by laser diffraction was 45.6 µm and 44.5 µm for HRW and SW flour, respectively. A flow agent helped the flour particles overcome the interparticle cohesive force during sieving and resulted in a smaller particle size with better size distribution. However, due to the higher cohesiveness of SW flour, flow agent at 0.5% of the sample mass had no effect on the measured mean particle size. Weibull and log-normal equations predicted the size distribution of flour with lower percent relative deviation compared to the Rosin-Rammler and Kumaraswamy equations.
Keywords: Particle size; Particle size distribution; Size distribution function; Wheat flour